Recent Advances in Chiral Aldehyde Catalysis for Asymmetric Functionalization of Amines - Wen, Wei; Guo, Qi-Xiang (Synthesis, 2022)
Asymmetric functionalization of amines and their derivatives is of great significance in synthetic chemistry and is widely used in the preparation of natural products and pharmaceuticals. In recent years, chiral aldehyde catalysis has emerged as a well-established and recognized tool, providing excellent catalytic activation and stereoselective control in asymmetric reactions of N-unprotected amino acid esters and amino acid ester analogues. In this short review, recent advances in enantioselective aldehyde catalysis, including chiral aldehydes as organocatalysts and co-catalysis combined with transition metals, will be summarized. Lastly, continued development of enantioselective aldehyde catalysis is prospected in the future.1 Introduction2 Chiral Aldehyde Catalysis for Tethering Strategy3 Chiral Aldehyde Catalysis for Imine Activation4 Chiral Aldehyde/Transition Metal Cooperative Catalysis5 Conclusion
Keywords: asymmetric catalysis; organocatalysis; chiral aldehyde catalysis; asymmetric functionalization; amines; amino acids